Accelerating agronomic impact through digital tools and public-private extension in Rwanda: smart fertilizer recommendations for potato - Mudereri, B.T.; Chernet, M.; Cyamweshi, A.R.; Kayumba, J.; Vandamme, E.; Uzamushaka, S.; Nshimiyimana, J.C.; Kreye, C.; Abera, W.; Aubert, C.; Borus, D.; Demo, P. (International Potato Center, 2024)
This report presents the validation process and findings for potato fertilizer recommendations developed by Rwanda Agricultural and Animal resources Board (RAB) together with CGIAR Excellence in Agronomy (EiA) initiative in collaboration with other stakeholders. This validation exercise aimed to ensure the recommendations' effectiveness in improving potato yield and soil health, aligned with Rwanda's agricultural priorities. The validation trials were conducted across key potato-growing regions in the northern and western districts of Rwanda to assess the applicability and effectiveness of the site-specific fertilizer recommendations in different agroecological zones. Key metrics evaluated included crop yield and cost-benefit analysis, providing a comprehensive understanding of the recommendations' economic and agronomic viability. The findings indicate a significant positive impact on potato yields when using site-specific fertilizer rates and application methods. Notably, these tailored fertilizer solutions optimized nutrient application, leading to increased efficiency and reduced input costs. The report also highlights feedback from farmers and extension workers, emphasizing the ease of adoption and the observable improvements in crop performance. Overall, the validation results underscore the potential of the SNS platform to enhance potato production sustainably in Rwanda. Recommendations for further refinement include expanding trial locations, integrating farmer feedback more systematically, and strengthening training initiatives to support widespread adoption of SNS recommendations.